Problem Base and Case Study Methodology in Medical Education - Zarnadze, Shalva; Zarnadze, Irine; Baramidze, Levan; Sikharulidze, Zurab; Tabidze, Devi; Bakradze, Tamar (European Scientific Journal, ESJ, 2018)
Objectives: EBM (Evidence-Based Medicine) and Case Study is a relatively new concept in medicine, and medical education, but one that is rapidly gaining acceptance as an important approach in assisting medical students, residents, and practicing physicians in their clinical decisionmaking. Problem Base and Case Study learning in Medical Education has become a widespread and effective method of using the medical literature. It has four basic steps: the development of a clinical question, the literature search for the appropriate medical literature to address the clinical question, critical appraisal of the acquired paper, and application of the results of the research paper to the patient at hand. Goals: Analysis of effectiveness of teaching methodology Methods: Observational Study Results: The use of PB(EBM) and CS should allow patient care that is the most effective, the most cost-effective, and the safest. The skills to master in use the EBM approach include that of question formulation, literature searching, critical appraisal of articles, and application of evidence. The resources needed include computers and Internet for access to full articles, a printer, and functional use of the English language. Moreover, this is a lifelong endeavor, so practice and mentorship are useful. The PB and CS component in the Tbilisi State Medical University has the aim of assisting students in learning objectives. Training in the PB and CS learning method will be provided at the beginning of the Module. Problem base and Case Study learning in education has become a widespread and effective method of literature use. It has four basic steps: the development of a clinical question, the Literature search for the appropriate medical literature to address the clinical question, critical appraisal of the acquired paper, and application of the results of the research paper to the patient at hand. Conclusion: By the end of this course you should have demonstrated your capacity to: recognize, compare, and contrast the general "ways of thinking" of science (biology) and of philosophy (ethics). Approach bioethical problems, break them into smaller component parts (analysis), and discuss those analyses through oral and written communication, both individually and in groups. Approach bioethical problems and propose solutions to them that transcend the disciplines of biology and philosophy, solidly rooted in their respective ways-of-knowing. Acquire and separate factual knowledge from opinion in the areas of science and philosophy. Demonstrate good critical thinking (that is, clear, logical (coherent and relevant), broad, deep, and discriminating) in bioethics through speaking and writing. Outcomes of PBL and CS are the problem-solving skills, self-directed learning skills, ability to find and use appropriate resources, critical thinking, measurable knowledge base, performance ability, social and ethical skills, self-sufficiency and self-motivation, leadership skills, ability to work on a team, communication skills, proactive thinking, congruence with workplace skills.